2011
DOI: 10.1073/pnas.1105100108
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal gene transfer facilitated the evolution of plant parasitic mechanisms in the oomycetes

Abstract: Horizontal gene transfer (HGT) can radically alter the genomes of microorganisms, providing the capacity to adapt to new lifestyles, environments, and hosts. However, the extent of HGT between eukaryotes is unclear. Using whole-genome, gene-by-gene phylogenetic analysis we demonstrate an extensive pattern of cross-kingdom HGT between fungi and oomycetes. Comparative genomics, including the de novo genome sequence of Hyphochytrium catenoides , a free-living sister of the oomycetes, shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
213
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(223 citation statements)
references
References 35 publications
10
213
0
Order By: Relevance
“…3C). This is in agreement with Richards et al (70,71) who showed that the closely related species Phytophthora ramorum acquired its extracellular ID-RCDs from filamentous ascomycetes through horizontal gene transfer.…”
Section: Discussionsupporting
confidence: 92%
“…3C). This is in agreement with Richards et al (70,71) who showed that the closely related species Phytophthora ramorum acquired its extracellular ID-RCDs from filamentous ascomycetes through horizontal gene transfer.…”
Section: Discussionsupporting
confidence: 92%
“…For all candidate gene fusions we calculated a phylogeny for each individual domain component of the gene fusion using a custom-built pipeline (35,36). We followed this pipeline analysis by a series of manual steps: BLAST checks of taxon sampling, multiple sequence alignment, alignment masking (37), amino acid substitution model selection (38), and tree calculation using PHYML with 100 bootstrap replicates (39).…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 10 genes were selected from a list of genes we favor for phylogenetic analysis (Table S4, gray shading). We then generated an alignment for each individual gene family using a modification of a custom built gene-by-gene phylogeny pipeline (35,36) integrating the trimAL (37) alignment masking tool. The resulting alignments were concatenated together using a custom Perl script.…”
Section: Methodsmentioning
confidence: 99%
“…Formation of transient hyphal or conidial anastomoses, direct uptake of DNA, presence of mobile elements in the vicinity of the transferred sequence and recombination have been proposed (Mehrabi et al 2011;Richards et al 2011;Fitzpatrick 2012). Richards et al (2009) showed that in two gene transfers from a fungus to the bryophyte moss Physcomitrella patens, the HGT was located near to a putative transposable element.…”
Section: Expression Of the Cu Gene In Geosmithia Speciesmentioning
confidence: 99%
“…lycopersici (Akagi et al 2009;Ma et al 2010). Finally, Richards et al (2011) showed how interkingdom gene transfer from filamentous fungi to oomycetes of at least 21 genes with roles in nutrient acquisition, degradation of plant surface components, and suppression of plant defences led to the appearance of plant pathogenic oomycetes.…”
Section: Introductionmentioning
confidence: 99%